Bomb Radiocarbon, Otolith Daily Increments and Length Modes Validate Age Interpretations of Chilean Jack Mackerel (Trachurus murphyi) - Cerna, Francisco; Moyano, Guillermo; Valero, Christian; Muñoz, Lizandro; Plaza, Guido; Campana, Steven E. (Frontiers in Marine Science, 2022)
Ages of Chilean jack mackerel (Trachurus murphyi) in the southern Pacific Ocean were validated using three methods: 1) daily microincrement readings in sagittal otoliths of young-of-the year (YOY) fish to validate the first annulus; 2) modal progression of strong year-classes (PSYC) to validate the first, second and third annuli, and 3) bomb radiocarbon analysis of otolith cores to validate the absolute age in older fish >38 cm fork length (FL). A Laird-Gompertz (LG) model was fitted to fork length (cm) at age (days) relationship in fish ranging from 3.4 to 23.0 cm FL and from 56 to 550 days in age. The LG model estimated a mean FL of 22 cm at the end of the first year of life, which was large compared with the mean FL estimated through conventional ageing in whole otoliths. The comparison between daily age with annual growth bands from whole otoliths, showed a false increment formed at 185±34 days and a second translucent increment formed at the 352±79 days, corresponding to the first annulus for fish with the mean FL of 21.4±1.8 cm. The PSYC coinciding with the recruits of 2008 (age 0), was tracked through three subsequent years with high accuracy, attaining 23, 27 and 30 cm FL in 2009, 2010 and 2011, respectively. These modes identified as age 1, age 2 and age 3 in the PSYC, matched to the mean length of fish with 2, 4 and 5 translucent increments in sagittal otoliths. Results from Bomb radiocarbon analysis evidenced most the ages were correct, because the ∆14C content of adult otolith core matched the reference chronology. The absolute mean ages for the assayed otoliths, based on the comparison with the reference chronology, ranged from 7 to 13 years for sizes between 39 and 60 cm FL. The age validation for T. murphy as addressed in the current study provided crucial information for enhancing stock assessment output of this important transboundary commercial species.